2010
DOI: 10.1093/annonc/mdq242
|View full text |Cite
|
Sign up to set email alerts
|

Combining gemcitabine, oxaliplatin and capecitabine (GEMOXEL) for patients with advanced pancreatic carcinoma (APC): a phase I/II trial

Abstract: This triple combination is feasible and, by far, met the predefined efficacy criteria warranting further investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…29 In contrast, recent data from prospective clinical trials have provided valid evidence for an intensification of combination chemotherapy in order to improve survival outcome (eg, by use of the FOLFIRINOX regimen). 3031 Thus, novel treatment strategies are urgently awaited and future preclinical and clinical research efforts should focus, for example, on the targeting of different pathways as well as on the improvement of translational research in order to identify and validate relevant targets and molecular pathways in PC. 3233 In contrast to the (preliminary) biomarker results of the PA.3 study, a higher rate of KRAS wild-type patients within our study cohort was observed (30% vs 21%), and the KRAS wild type status was associated with an improved OS in our patient population (of which FFPE tissue was available).…”
Section: Discussionmentioning
confidence: 99%
“…29 In contrast, recent data from prospective clinical trials have provided valid evidence for an intensification of combination chemotherapy in order to improve survival outcome (eg, by use of the FOLFIRINOX regimen). 3031 Thus, novel treatment strategies are urgently awaited and future preclinical and clinical research efforts should focus, for example, on the targeting of different pathways as well as on the improvement of translational research in order to identify and validate relevant targets and molecular pathways in PC. 3233 In contrast to the (preliminary) biomarker results of the PA.3 study, a higher rate of KRAS wild-type patients within our study cohort was observed (30% vs 21%), and the KRAS wild type status was associated with an improved OS in our patient population (of which FFPE tissue was available).…”
Section: Discussionmentioning
confidence: 99%
“…A Phase I and II clinical study involving patients with an advanced PC being treated with a combination of Capecitabine and Gemcitabine was regarded as a part of our study. Administering a combined therapy between Gemcitabine, oxaliplatin, and Capecitabine for advanced PC gave us results of 4.3‐month median PFS, 7.8‐month median OS of patients, and 8.9‐month median OS in patients signifying good performance; as first‐line treatment of inoperable or metastatic PC with Gemcitabine and Capecitabine, it presented with a median OS of 8 months (Hess et al, ; Scheithauer et al, ; Schilsky, Bertucci, Vogelzang, Kindler, & Ratain, ; Stathopoulos et al, ). The foundation of the combination of 5‐FU with CI and Gemcitabine is to prolong thymidylate synthetase inhibition, thereby increasing the chance of pharmacodynamic with Gemcitabine and reducing the toxicity compared to 5‐FU bolus (Di Costanzo et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Before each chemotherapy cycle all patients underwent routine work-up including physical examination, blood tests and treatment-induced adverse effects assessment. IPCT regimens included modified FOLFOXIRI [27], GEMOX or GEMOXEL [28,29].…”
Section: Methodsmentioning
confidence: 99%